PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 2 GUNUNGSITOLI PADA KURIKULUM MERDEKA - Telaumbanua, Happy Rahmat Saro; Telaumbanua, Yakin Niat; Mendrofa, Ratna Natalia; Mendrofa, Netti Kariani (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
This research is based on the results of a preliminary study conducted by the researcher at SMP Negeri 2 Lotu, which found several problems, namely (1) the low numeracy literacy skills of students, due to the lack of variation in the learning models used by teachers, and (2) the low interest in learning mathematics among students. The purpose of this study is to determine: (1) the effect of the project based learning model on students' numeracy literacy, and (2) the effect of the project based learning model on students' interest in learning mathematics. This research is a quantitative study using a quasi-experimental method with a nonequivalent control group design. The population in this study was all seventh-grade students, and the sample consisted of two classes: class VII-A as the experimental class and VII-B as the control class. The research instruments used were tests and questionnaires. The results of the study showed that: (1) The numeracy literacy result obtained a thitung value of 9.849 and ttabel value of 2.017, because thitung ttabel, H₀ is rejected and H₁ is accepted. (2) The result for students’ learning interest obtained a thitung value of 20.753 and ttabel value of 2.017, because thitung ttabel, H₀ is rejected and H₁ is accepted. It can be concluded that: (1) The project based learning model had a significant effect on students’numeracy literacy. This is shown by the post-test average score of the experimental group being 78 (high category), which is higher than the control group’s score of 63,56 (moderate category). (2) The project based learning model also had a significant effect on students’ interest in learning mathematics. The average score of the learning interest questionnaire in the experimental group reached 89,40 (very high category), while the control group only reached 55,78 (moderate category).